A study of preschool teachers’ job satisfaction and their turnover intention in Penang - Teoh, Melanie Ruochy (2023)
The demanding nature of the preschool teaching profession, both physically and mentally, contributes to high turnover rates. Unfortunately, it often struggles underappreciation, highlighting disparity in its perceived value. Valuing preschool teachers’ role is essential for their well-being and job satisfaction, which is closely related to its high turnover issue. However, there is a limited relevant research in the local context. Hence, the current study examined the level of job satisfaction and turnover intention of preschool teachers in Penang. The study also investigates the relationship between preschool teachers’ total job satisfaction and their turnover intention, specifically focuses on the nine subscales of job satisfaction, namely pay, promotion, supervision, fringe benefits, contingent rewards, operating conditions, coworkers, nature of work and communication. This research adopted Herzberg's Two-Factor Theory as theoretical framework and employed a quantitative correlational design. Utilizing the Spector’s (1985) Job Satisfaction Survey (JSS) and the Roodt’s (2004) Turnover Intention Scale (TIS-6) as research instrument, the study was conducted using convenient sampling involving 64 preschool teachers in Penang. The study revealed a significant negative correlation between preschool teachers' total job satisfaction and their turnover intention (r =-.736**, p